Case Report: MIS-C With Prominent Hepatic and Pancreatic Involvement in a Vaccinated Adolescent – A Critical Reasoning - Consolini, Rita; Costagliola, Giorgio; Spada, Erika; Colombatto, Piero; Orsini, Alessandro; Bonuccelli, Alice; Brunetto, Maurizia R.; Peroni, Diego G. (Frontiers in Pediatrics, 2022)
Multisystem inflammatory syndrome in children (MIS-C) is a pathologic condition that has emerged during the coronavirus disease 2019 (COVID-19) pandemic. Although the epidemiological evidence of association between MIS-C and SARS-CoV-2 infection has been demonstrated, its pathogenic mechanism is still undefined. We describe the case of a 17-year old female, previously vaccinated against SARS-CoV-2, presenting with a history of asthenia, fever, cough, anorexia, abdominal pain, and vomiting. During the hospitalization, the patient developed bilateral conjunctivitis, hand vasculitis, cutaneous rash, and multiple pulmonary nodules, following by hepatitis and pancreatitis. As she reported a high-risk contact with a SARS-CoV-2 positive patient 10 days before admission, the epidemiological link and the clinical picture characterized by multi-system organ disfunction and inflammatory biomarkers increase led us to the diagnosis of MIS-C. Therefore, the patient was treated with intravenous immunoglobulin and corticosteroids, resulting in a rapid resolution of fever, cutaneous, and pulmonary involvement, while the recovery of hepatitis and pancreatitis was observed in the following weeks. This case leads to the discussion on whether SARS-CoV-2 immunized children and adolescents should be considered at risk of developing MIS-C and on their possible presentation with non-classic clinical features. Additionally, due to the increasing number of vaccinated children and adolescents, the issues resulting either from the diagnostic suspect of MIS-C or from the consequent need of an early therapeutic approach are discussed.